Role of Corin in Blood Pressure Regulation in Normotensive and Hypertensive Pregnancy: A Prospective Study. Issue 2 (February 2019) - Badrov, Mark B.; Park, Sun Young; Yoo, Jeung-Ki; Hieda, Michinari; Okada, Yoshiyuki; Jarvis, Sara S.; Stickford, Abigail S.; Best, Stuart A.; Nelson, David B.; Fu, Qi
Abstract : Corin (an atrial natriuretic peptide–converting enzyme) represents a potential biomarker for gestational hypertensive disorders; yet, its role in blood pressure (BP) regulation throughout pregnancy remains unclear. We investigated the time course of change in blood corin content in relation to BP and sympathetic nerve activity throughout pregnancy. Forty-four women (29±0.9 years) participated. Following-term, 23 had low-risk (no personal history of gestational hypertensive disorders) normal pregnancies, 13 had high-risk (personal history of gestational hypertensive disorders) normal pregnancies, and 8 developed gestational hypertension. BP, heart rate, muscle sympathetic nerve activity, and serum corin were measured before pregnancy, during early (4–8 weeks) and late pregnancy (32–36 weeks), and postpartum (6–10 weeks). Overall, compared with prepregnancy, corin remained unchanged during early pregnancy, increased markedly during late pregnancy ( P <0.001), and returned to prepregnancy levels postpartum. In women who developed gestational hypertension, the change in corin from early to late pregnancy was greater than those with low-risk normal pregnancies (Δ971±134 versus Δ486±79 pg/mL; P <0.05). Throughout pregnancy, BP and muscle sympathetic nerve activity were augmented in women with gestational hypertension (all P <0.05). Finally, changes in corin from early to late pregnancy were related to all indices of BP ( R =0.454–0.551; all P <0.01) in late pregnancy, whereas burst frequency, burst incidence, and total muscle sympathetic nerve activity ( R =0.576–0.614; all P <0.001) in early pregnancy were related to changes in corin from early to late pregnancy. Corin plays a unique role in BP regulation throughout normotensive and, especially, hypertensive pregnancy and may represent a promising biomarker for determining women at high risk of adverse pregnancy outcome.